Acute Asymptomatic Vasculitic Infarct in Patients with Meningitis - Madhavrao, Vikhe Pramod (Journal of Contemporary Medical Practice, 2024)
Tuberculous meningitis (TBM) is the most life - threatening form of extrapulmonary tuberculosis and the most common presentation of neurotuberculosis. TBM patients with infarcts are reported to be three times more fatal than patients without infarct. Contrast enhanced magnetic resonance imaging (MRI) is more sensitive than CT for the detection of ischemic changes, edema secondary to inflammation and basal meningeal inflammation. we reviewed the acute asymptomatic vasculitic infarct (by DWI MRI brain imaging) in 41 patients with tuberculous meningitis encountered during a 2 year period. MRI DWI imaging shows asymptomatic acute vasculitic infarct in 13 patients (31%). Thalamus was the most common site of infarct found in 7 patients (53.84%) followed by basal ganglion in 4 patients (30.76%). One patient had uncal (7.6%) and 1 patient had splenium infarct.